2020
DOI: 10.1038/s41598-020-69817-y
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric lung nodule segmentation using adaptive ROI with multi-view residual learning

Abstract: Byung-il Lee 2 & Yeong-Gil Shin 1 Accurate quantification of pulmonary nodules can greatly assist the early diagnosis of lung cancer, enhancing patient survival possibilities. A number of nodule segmentation techniques, which either rely on a radiologist-provided 3-D volume of interest (VOI) or use the constant region of interests (ROIs) for all the slices, are proposed; however, these techniques can only investigate the presence of nodule voxels within the given VOI. Such approaches restrain the solutions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…U-Net and Fully Convolutional Neural Networks (FCN) architectures are two basic structures that are frequently used. Numerous works have shown that convolutional neural networks architecture can significantly improve the performance of lung segmentation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], especially semantic segmentation networks such as FCN [ 61 ] and U-Net [ 62 ]. Such networks implement two key steps.…”
Section: Lung Nodule Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…U-Net and Fully Convolutional Neural Networks (FCN) architectures are two basic structures that are frequently used. Numerous works have shown that convolutional neural networks architecture can significantly improve the performance of lung segmentation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], especially semantic segmentation networks such as FCN [ 61 ] and U-Net [ 62 ]. Such networks implement two key steps.…”
Section: Lung Nodule Segmentationmentioning
confidence: 99%
“…The proposed model was trained and validated on the LUNA16 dataset and achieved 0.736 DSC. Usman et al [ 56 ] proposed a dynamic modification region of interest (ROI) algorithm. This approach used Deep Res-UNet as the foundation for locating the input lung nodule volumes and improving lung nodule segmentation.…”
Section: Lung Nodule Segmentationmentioning
confidence: 99%
“…Various studies [120]- [122] have used computer vision algorithms to speed up the process of disease detection across several imaging modalities with some studies demonstrating that image analysis techniques have the potential to outperform expert radiologists [123], [124]. To diagnose COVID-19, two medical imaging modalities (CT and X-ray) have been experimented with [125], which we discuss below.…”
Section: A Image Data Analysismentioning
confidence: 99%
“…Detection of a lung nodule, segmentation and classification only based on simple morphological and textural properties such as size or texture or shape features is not robust as suggested by Paing et al [38] and does not reveal the exact magnitude of the underlying challenges in lung cancer detection and diagnosis. Researchers have used various techniques for lung nodule detection and segmentation such as 3D tensor filtering with local image feature analysis [18], global optimal active contour model [54], corner seeded region growing combined with differential evolution based optimal thresholding [35], connected component labelling with morphological operations and multilayer perceptron [21], sparse field level sets and boosting algorithm [39], adaptive ROI with multi-view residual learning [49], LBF active contour model with information entropy and joint vector [22] etc. including optical flow methods for evaluation of interval change in metastatic lung nodules [17], and segmentation by background subtraction [45].…”
Section: Challenges To Lung Cancer Detectionmentioning
confidence: 99%